Development of Local History E-Module based on Dieng Temple Site for Students of SMA N 1 Bawang, Banjarnegara Regency - Dwi Oktaviana; R. Soeharso (Universitas Islam Negeri Sumatera Utara, 2026)
This research aims to develop learning media in the form of Dieng Temple Site-Based Local History E-module for grade X students at SMA Negeri 1 Bawang, Banjarnegara Regency, and assess the feasibility of the media produced. The method used in this study is Research and Development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages, but is limited to the develop stage. The research subjects consisted of 30 students in class X-1. Data collection techniques were carried out through interviews, observations, and questionnaires. The results of the study show that e-modules have a very high level of feasibility. This is shown by the results of the validation of material experts (96.2%), media experts (88.2%), and the assessment of history teachers (98.7%). In addition, the results of the student response questionnaire showed a percentage of 91.4% and were categorized as